HUBUNGAN PEMBERIAN MAKAN BAYI DAN ANAK (PMBA) DENGAN KEJADIAN STUNTING PADA ANAK USIA 2-5 TAHUN DI DESA SEMEMU KABUPATEN LUMAJANG - Wardani, Wuri Astrida Kusuma; Ermawati, Iit; Sary, Yessy Nur Endah (NHM PRESS, 2023)
Stunting is caused by chronic malnutrition, recurrent infections over a prolonged period, and a lack of psychosocial stimulation during pregnancy and after birth. Stunting is not solely caused by a specific nutritional factor. This study aims to determine the correlation between infant and child feeding practices and stunting incidence among children aged 2-5 years in Sememu Village, Lumajang Regency. This study utilized a descriptive method with retrospective data collection. The population consisted of 100 respondents, and a sample of 80 respondents was selected using random sampling technique. The statistical analysis used was the Spearman's rho correlation test. The results of the study revealed that the majority of respondents had good infant and child feeding practices, with 51 respondents (63.8%) falling into the